The role of vitamin E In reducing the side effects of Gabapentin on some physiological parameters related to the heart in male albino rats - Hassoun, Sarah A.; Mahood, Hanaa E. (Edelweiss Applied Science and Technology, 2024)
The study was designed to evaluate the role of vitamin E in reducing the side effects of gabapentin on some physiological parameters related to the heart in male albino rats,(30) males were used, who were divided into three equal groups : The control group was given physiological saline solution in concentration( 0.9% ), the treatment group T1 was given gabapentin at a concentration of (100mg / Kg) of body weight, treatment group (T2) was given gabapentin at a concentration of (100mg / Kg) of body weight and vitamin E at a concentration of 80 mg/kg of body weight, the results revealed that gabapentin causes significant increase in some parameters related to the heart,Vitamin E helped reduce them.